TANGGUNG JAWAB HUKUM PENYIDIK KEPOLISIAN TERHADAP BARANG BUKTI YANG KURANG LENGKAP - Trisna Dewi, Ni Made (VYAVAHARA DUTA, 2021)
Examination of cases before the trial, as well as in the preliminary examination, there are many problems related to evidence. Although evidence has an important role in a criminal case, it is not that the presence of evidence is absolutely necessary in a criminal case. Where the judge in making a decision does not always rely on evidence because it only happens case by case, or it can be said that not all cases can be resolved just because of the evidence. The formulation of the problem raised in this study is what is the legal basis for the police against incomplete evidence and what is the legal responsibility of the police for incomplete evidence. This type of research is empirical legal research. This research uses an approach that examines the prevailing laws and regulations, legal theory, and can be in the form of scholars' opinions related to problems in this scientific paper, namely the legal responsibility of the police for incomplete evidence. The conclusion of this research is that the legal basis of the police for incomplete evidence is Article 110 paragraph (2) and (3) and Article 138 paragraph (2) of the Criminal Procedure Code where the Public Prosecutor returns the case file to the investigator to complete the case file concerned. In returning the case file, the Public Prosecutor is also required to provide instructions regarding the incompleteness of the case file, both regarding the completeness of the case file clearly and clearly so that it can be understood by the Investigator.Keywords: Responsibility, police, incomplete evidence